Coaching for wellbeing, productivity, and innovation using perception coaching with individuals, teams, and organizations - Bengtson, Barbara J. (Routledge, 2024)
"This book presents perception coaching as a model that enables coaches to support their clients in understanding the impact of their attitudes in themselves, helping individuals, teams, and organizations reduce their inherent biases to more effectively collaborate, innovate, and support each other. Dr. Bengtson approaches coaching through the lens of educational psychology in three parts, starting with understanding self and others, moving on to interactions and teams, and finally culture and organizations. Filled with strategies throughout, the book focuses on examining natural patterns of thinking and acting to uncover perceptual filters so that the unexamined and unexplained may be brought to light and understood. Covering topics such as emotional intelligence and communication styles, the book aims to help coaches support their clients pursue purpose, increase inclusion, and create innovation. This book is invaluable reading for current and aspiring coaches, non-profit and corporate leaders, as well as talent development professionals"-- Provided by publisher.